Considering humor by way of Castelao’s laughter - Caamaño, Juan (Madrygal. Revista de Estudios Gallegos, 2013)
By means of a selective analysis of Alfonso Rodríguez Castelao’s work, this article examines the problem of humor. The humorist’s graphic and literary work equally allow us to discern –in opposition to the commonplace view that sees only the positive effects of humor in both art and life– that humor is a matter of politics and ideology. For this reason, a critical stance towards humor is not enough; rather, a unique kind of humor is necessary. The value of Castelao’s work resides precisely in the fact that it bears the prospect of a genuinely alternative humor, one that can serve as a stimulus to better understand the world in which we live.